Vitamin D Supplementation and the Risk of Colds in Patients with Asthma - Denlinger, Loren C. (Am J Respir Crit Care Med, 2016)
Rationale: Restoration of vitamin D sufficiency may reduce asthma exacerbations, events that are often associated with respiratory tract infections and cold symptoms. Objectives: To determine whether vitamin D supplementation reduces cold symptom occurrence and severity in adults with mild to moderate asthma and vitamin D insufficiency. Methods: Colds were assessed in the AsthmaNet VIDA (Vitamin D Add-on Therapy Enhances Corticosteroid Responsiveness) trial, in which 408 adult patients were randomized to receive placebo or cholecalciferol (100,000 IU load plus 4,000 IU/d) for 28 weeks as add-on therapy. The primary outcome was cold symptom severity, which was assessed using daily scores on the 21-item Wisconsin Upper Respiratory Symptom Survey. Measurements and Main Results: A total of 203 participants experienced at least one cold. Despite achieving 25-hydroxyvitamin D levels of 41.9 ng/ml (95% confidence interval [CI], 40.1–43.7 ng/ml) by 12 weeks, vitamin D supplementation had no effect on the primary outcome: the average peak WURSS-21 scores (62.0 [95% CI, 55.1–68.9; placebo] and 58.7 [95% CI, 52.4–65.0; vitamin D]; P = 0.39). The rate of colds did not differ between groups (rate ratio [RR], 1.2; 95% CI, 0.9–1.5); however, among African Americans, those receiving vitamin D versus placebo had an increased rate of colds (RR, 1.7; 95% CI, 1.1–2.7; P = 0.02). This was also observed in a responder analysis of all subjects achieving vitamin D sufficiency, regardless of treatment assignment (RR, 1.4; 95% CI, 1.1–1.7; P = 0.009). Conclusions: Our findings in patients with mild to moderate asthma undergoing an inhaled corticosteroid dose reduction do not support the use of vitamin D supplementation for the purpose of reducing cold severity or frequency.